Tuberculosis of Pubic Symphysis – A Case Report - Sarfraz, Tariq; Alkarim, Fizzah; Iqbal, Soman Nadim; Aslam, Menal; Aneeqa, Saba (Pakistan Armed Forces Medical Journal, 2023)
Tuberculosis is one of the major health issues in developing countries, including Pakistan, causing significant morbidity and mortality. As far as extra-pulmonary sites of tuberculosis are concerned, pubic symphysis is a relatively uncommon site. We are reporting a unique case of tuberculosis at this rare site. A 42-year-old female reported complaints of groin pain, fever and numbness in their legs for one day. After all the investigations, the patient was put on a quadruple Anti-Tuberculosis Therapy(ATT) according to the National Institute of Health and Care Excellence (NICE) guidelines. The patient completed the ATTcourse for seven months and was symptom-free. She was advised to follow up on a CT scan after three months to look for a recurrence of the infection.